2021
DOI: 10.3390/ijerph18115832
|View full text |Cite
|
Sign up to set email alerts
|

Wellbeing of Indigenous Peoples in Canada, Aotearoa (New Zealand) and the United States: A Systematic Review

Abstract: Despite the health improvements afforded to non-Indigenous peoples in Canada, Aotearoa (New Zealand) and the United States, the Indigenous peoples in these countries continue to endure disproportionately high rates of mortality and morbidity. Indigenous peoples’ concepts and understanding of health and wellbeing are holistic; however, due to their diverse social, political, cultural, environmental and economic contexts within and across countries, wellbeing is not experienced uniformly across all Indigenous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 115 publications
(1,373 reference statements)
1
23
1
Order By: Relevance
“…Family, kinships and community connections are important to the wellbeing of Indigenous peoples in Australia [ 6 , 10 , 11 ], and globally [ 21 ]. In this study, wellbeing was lowest among those without partners or living on their own.…”
Section: Main Textmentioning
confidence: 99%
“…Family, kinships and community connections are important to the wellbeing of Indigenous peoples in Australia [ 6 , 10 , 11 ], and globally [ 21 ]. In this study, wellbeing was lowest among those without partners or living on their own.…”
Section: Main Textmentioning
confidence: 99%
“…Conceptions of wellbeing are culturally bound and shaped by a person's experiences, beliefs and values [5]. Whilst understandings do vary across cultural groups, Indigenous peoples globally commonly hold holistic and collectivist worldviews that prioritise the wellbeing of the group above one's own individual needs [6][7][8], differing markedly from the dominant Western individual-centric worldview. Furthermore, many Indigenous peoples share similar histories of colonisation and trauma [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing intergenerational legacies of colonisation, including the disruption of family and kinship networks, loss of language and culture, and social marginalisation, impact the experience and conception of wellbeing for Indigenous peoples [9]. Many parts of life influence Indigenous peoples' wellbeing, and these parts are often described by Indigenous people, globally, as being deeply and inextricably interconnected [8,10]. For example, Kilcullen et al (2016) identified connectedness to country, family and kinship, cultural knowledge and social networks as contributing to the health and wellbeing of Aboriginal and Torres Strait Islander people in Australia [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting Special Issue includes 31 papers in total, with 21 from Australia [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], 4 from the United States [ 28 , 29 , 30 , 31 ], 3 from Aotearoa/New Zealand [ 32 , 33 , 34 ], 1 from Canada [ 35 ], and 2 from authors in multiple countries [ 36 , 37 ]. This represents a substantial body of research on the health and wellbeing of Indigenous and Tribal peoples, possibly the largest collection ever published.…”
Section: Introduction—why This Special Issue?mentioning
confidence: 99%